Digital Promotion Strategies Utilizing Social Media to Improve the Image of Educational Institutions - Suprihartini; Purwoko; Widyatmike Gede Mulawarman; Nurlaili; Masrur Yahya (Journal of Educational Management Research, 2025)
The rapid advancement of digital technology urges educational institutions to innovate in promotional strategies, particularly through the utilization of social media. Social media offers broad, flexible, and easily accessible channels for reaching potential students and improving institutional image. This mix method explores the implementation of digital promotion strategies using social media, supported by both primary data (observations and student questionnaires) and secondary sources. The findings reveal that optimized use of digital platforms significantly enhances public awareness and interest in educational institutions. Instagram emerged as the most influential platform, with 91.6% of users obtaining information through it, followed by the official website at 61.4%. The engagement rate is substantial, with 25.3% of users accessing content daily and 30.1% weekly. This digital engagement correlates with a noticeable increase in prospective student applications—from 3,328 to 3,788. The study contributes to the understanding of effective digital branding strategies in the education sector, particularly in the digital era.